2017
DOI: 10.1007/s10029-017-1699-3
|View full text |Cite
|
Sign up to set email alerts
|

Trocar site hernia following laparoscopic cholecystectomy: a 10-year single center experience

Abstract: The incidence of TSH following LC is considerably low. Obesity is an independent risk factor for TSH development, while closure of fascial incision of 10 mm below the xiphoid is not justified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
12
1
2
Order By: Relevance
“…All of the previous factors were found significant on univariate analysis. However, on multivariate analysis the list of significance was shortened to advancing age (>70), BMI > 30, duration of surgery, diabetes mellitus, incision enlargement, and wound infection as detailed in Table 3 7,10,11 .…”
Section: Pt Nomentioning
confidence: 99%
“…All of the previous factors were found significant on univariate analysis. However, on multivariate analysis the list of significance was shortened to advancing age (>70), BMI > 30, duration of surgery, diabetes mellitus, incision enlargement, and wound infection as detailed in Table 3 7,10,11 .…”
Section: Pt Nomentioning
confidence: 99%
“…Memon et al 8 described an incidence of 0.11% and 3.66% in port-site hernia comparing epigastric and umbilical port site to retrieve the gallbladder. Similarly, Chatzimavroudis et al 24 found a higher rate of short-and long-term complications in the umbilical port-site extraction cohort. Our meta-analysis shows no statistically significant differences among groups (epigastric vs umbilical ports) in terms of hernia incidence, postoperative infections rate, nor the operative time.…”
Section: Discussionmentioning
confidence: 74%
“…Although some surgeons close all trocar site fascial defects, [17] many surgeons do not routinely close them. [9] In a 1172 case, Chatzimavroudis et al, [18] despite routine closure of fascia, found TSH ratios as 0.6% and 0.94% in the first and second years, respectively. Nassar et al [19] reported the incidence of TSH was 1.8% in patients with preoperative umbilical hernia even if the defect was closed primary.…”
Section: Discussionmentioning
confidence: 96%